Livestock Feeding Challenges, Alternative Strategies, and Waste-to-Feed Innovations in the Nepalese Livestock Sector: A Review - Acharya, Arjun (Journal of Nepal Agricultural Research Council, 2025)
Nepal’s livestock sector plays a vital role in ensuring food security, supporting rural livelihoods, and driving economic growth; however, feed shortages, rising costs, and inefficient waste management remain significant challenges. This review explores the potential of waste-to-feed innovations as a sustainable strategy within a circular bioeconomy approach. It outlines the current status of feed resources and explores opportunities to transform agro-industrial by-products, food waste, and animal by-products into nutritionally valuable feed ingredients. Advanced methods such as microbial fermentation, insect-based protein production, and enzymatic conversion of lignocellulosic biomass are discussed for their roles in enhancing feed quality and decreasing reliance on traditional feed sources. Emerging thermal and non-thermal processing technologies, along with their environmental advantages and socio-economic impacts, including cost savings, waste valorization, and employment creation, are also explored. Policy and institutional support from the Ministry of Agriculture and Livestock Development, the Department of Livestock Services, and the Nepal Agricultural Research Council is vital in this aspect; however, challenges related to safety regulations, quality assurance, and research data gaps remain. Therefore, the adoption of waste-to-feed technologies in Nepal represents a transformative opportunity to reduce environmental burdens and foster sustainable rural entrepreneurship. Coordinated policies, research partnerships, and capacity-building are essential to realizing a resilient, circular livestock production system.